2001
DOI: 10.1021/ja011357l
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Tautomers and Conformers of Neutral and Protonated Arginine

Abstract: The relative stabilities of zwitterionic and canonical forms of neutral arginine and of its protonated derivative were studied by using ab initio electronic structure methods. Trial structures were first identified at the PM3 level of theory with use of a genetic algorithm to systematically vary geometrical parameters. Further geometry optimizations of these structures were performed at the MP2 and B3LYP levels of theory with basis sets of the 6-31++G** quality. The final energies were determined at the CCSD/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
210
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(225 citation statements)
references
References 42 publications
(112 reference statements)
12
210
1
1
Order By: Relevance
“…If the peptide ions were present as zwitterions, then we would expect some variation in the collision cross-sections for the peptide and methyl ester ions owing to a reduction in the interaction between charge sites [47,48]. Our molecular dynamics simulation and molecular orbital calculations also suggest that charge-solvated species represent the most stable conformations of the [M ϩ H] ϩ ions, which is consistent with Simon's studies [31]. Theoretical collision cross-sections for [M ϩ H] ϩ ions for arginine-containing di-and tripeptide and C-terminal methylated derivatives (see Table 2) were calculated by using Mobcal [49].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…If the peptide ions were present as zwitterions, then we would expect some variation in the collision cross-sections for the peptide and methyl ester ions owing to a reduction in the interaction between charge sites [47,48]. Our molecular dynamics simulation and molecular orbital calculations also suggest that charge-solvated species represent the most stable conformations of the [M ϩ H] ϩ ions, which is consistent with Simon's studies [31]. Theoretical collision cross-sections for [M ϩ H] ϩ ions for arginine-containing di-and tripeptide and C-terminal methylated derivatives (see Table 2) were calculated by using Mobcal [49].…”
Section: Resultssupporting
confidence: 89%
“…We assumed that protonation occurred on the guanidine group owing to the high proton affinity (PA ϭ 251.2 kcal/mol) for arginine [23], but we also considered whether the most stable structure of the [M ϩ H] ϩ ion is a charge-solvated species, as suggested by Simon et al [31], or zwitterionic species, as suggested by Strittmatter and Williams [28]. To address this question, we used a combination of collision cross-sections obtained by using ion mobility spectrometry (IMS) [45] [46].…”
Section: Resultsmentioning
confidence: 99%
“…Because of the coarse grid in its first step, the SUMM approach turned out to be inefficient for such a situation. The success of the remaining algorithms is compared in Figure 4, which gives the relative RI-MP2/TZVPP//B3LYP/ TZVPP energies of the generated conformers with respect to structure (C5) given by Rak et al 5 For a better comparison only the MMFF94 conformers are given. As one can see in Figure 4 the stochastic MCMM algorithm produces only one conformer that is lower in energy than C5.…”
Section: Conformational Search Strategiesmentioning
confidence: 99%
“…As noted before, the structures C5 and Z3 were already described in the literature. 5 Furthermore, the multiple hydrogen binding patterns within the stacked structures comprehend hydrogen bonds of the type NÀ ÀHÁÁÁO from the guanidine to the protonated hydroxyl oxygen (N1, N3, N4). Such hydrogen bond types have not been mentioned for the arginine monomer yet.…”
Section: Electronic Structure Optimizationsmentioning
confidence: 99%
See 1 more Smart Citation